Efektivitas Kebijakan Pengelolaan Sampah di Kecamatan Tegal Rejo - Sitompul, Yunike Sarah; Sianipar, Lumongga; Sembiring, Febiola; Simanullang, Alfon Apriel; Ivanna, Julia (Majalah Ilmiah METHODA, 2024)
Waste management  policies require cooperation between implementing agencies such as district, sub-district, village and community governments. Hierarchical coordination between implementing agencies is required to facilitate the flow of information. qualitative method with descriptive study research type. The data collection techniques used are observation, documentation, interviews which are also supported by relevant references. This research method adopts a qualitative approach which involves in-depth analysis of the data. Tegal Regency has technological limitations, which affect the effectiveness of the waste management system. Only one sub-district has a waste shredding machine, and there are limitations. The conclusions that can be drawn from the problems that researchers have studied. Overall, the implementation of waste management policies in Tegal Rejo District is still not optimal.